2019
DOI: 10.1073/pnas.1816620116
|View full text |Cite|
|
Sign up to set email alerts
|

Visualizing the iron atom exchange front in the Fe(II)-catalyzed recrystallization of goethite by atom probe tomography

Abstract: The autocatalytic redox interaction between aqueous Fe(II) and Fe(III)-(oxyhydr)oxide minerals such as goethite and hematite leads to rapid recrystallization marked, in principle, by an atom exchange (AE) front, according to bulk iron isotopic tracer studies. However, direct evidence for this AE front has been elusive given the analytical challenges of mass-resolved imaging at the nanoscale on individual crystallites. We report successful isolation and characterization of the AE front in goethite microrods by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 54 publications
1
69
1
Order By: Relevance
“…The distribution of the isotopic label 57 Fe (blue) has been emphasised (Taylor et al . ); (f) pyrite specimen showing the distribution of As (Purple), Ni (Yellow) and Sb (Green). The trace elements are organised in an array of dislocations (unpublished data set from Fougerouse et al .…”
Section: Geoscience Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of the isotopic label 57 Fe (blue) has been emphasised (Taylor et al . ); (f) pyrite specimen showing the distribution of As (Purple), Ni (Yellow) and Sb (Green). The trace elements are organised in an array of dislocations (unpublished data set from Fougerouse et al .…”
Section: Geoscience Applicationsmentioning
confidence: 99%
“…, Hellmann et al 2015, Gin et al 2017, diamond(Heck et al 2014, Lewis et al 2015, Schirhagl et al 2015, Mukherjee et al 2016, Fe-Ni metal alloys(Einsle et al 2018) and silicides(Gopon et al 2017), platinum-group alloys(Parman et al 2015, Daly et al 2017, oxides(Bachhav et al 2011, Fahey et al 2016, Taylor et al 2018, Frierdich et al 2019, Gamal El Dien et al 2019, Genareau et al 2019, Taylor et al 2019, carbonates(Felmy et al 2015, Branson et al 2016, P erez- Huerta et al 2016, P erez-Huerta and Laiginhas 2018, sulfides, Dubosq et al 2019, Gopon et al 2019, Wu et al 2019, sulfates(Weber et al 2016), zeolites(Schmidt et al 2019) and rock-forming silicates, such as feldspars(White et al 2018c, Cao et al 2019) and olivine(Bloch et al 2019, Cukjati et al 2019 …”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Under anoxic to sub-oxic, non-sulphide rich environments, microbial respiration leads to the generation of Fe(II) (aq) which can react with iron(III) oxy-hydroxides to form more thermodynamically stable phases or induce recrystallization and growth within hours to days. 13,[20][21][22][23] For bacterial mediated reduction of 2-line FH, various reaction mechanisms have been proposed that include: (1) electron transfer through direct contact between the cell wall and FH surface, (2) electron shuttling of soluble chelating agents such as humic acid, quinones, and avins with a "labile Fe(III) phase/reactive-FH" and/or 2-line FH and (3) through extracellular nano-wires. 13,17,24 In the case of the abiotic reduction of 2-line FH with Fe(II) (aq) , it has been generally agreed upon that the 2-line FH transformation to more thermodynamically stable phases (LP, GT, MG, and HT) is dependent upon several experimental variables.…”
Section: Introductionmentioning
confidence: 99%
“…13,20,21,29 Though more detailed research has indicated that the major reaction steps in current proposed conceptual models comprise of (1) the adsorption of Fe(II) (aq) onto 2-line FH, (2) immediate oxidation of Fe(II)-2-line FH to Fe(III) with electron exchange to other Fe(III) lattice atoms, (3) atom exchange at the interface of the redox couple in step 2, (4) electron conduction through the solid, (5) the production of a "reactive surface FH/labile Fe(III)", (6) reductive release of Fe(II) (aq) , (7) continuing cycle of 1-6 until LP, GT, MG or HT are precipitated on the surface of the "reactive-FH/labile Fe(III) phase" and nally (8) complete bulk transformation of the initial 2-line FH to LP, GT, MG or HT that depends upon the experimental conditions. 20,21,23,29,30 Evidence for these more detailed steps in conceptual models have come from decades of research via the use of solution (e.g. ICP-OES/ MS, AAS, UV-VIS, isotope labelling, adsorption models), solid (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation